Improvement of Physical Performance Following a 6 Week Change-of-Direction Training Program in Elite Youth Soccer Players of Different Maturity Levels - Sariati, Dorsaf; Hammami, Raouf; Zouhal, Hassane; Clark, Cain C. T.; Nebigh, Ammar; Chtara, Mokhtar; Chortane, Sabri Gaied; Hackney, Anthony C.; Souissi, Nizar; Granacher, Urs; Ounis, Omar Ben (Frontiers in Physiology, 2021)
Background: Change-of-direction (CoD) is a necessary physical ability of a field sport and may vary in youth players according to their maturation status. Objectives: The aim of this study is: to compare the effectiveness of a 6-week CoD training intervention on dynamic balance (CS-YBT), horizontal jump (5JT), speed (10 and 30-m linear sprint times), CoD with (15 m-CoD + B) and without (15 m-CoD) the ball, in youth male soccer players at different levels of maturity [pre- and post-peak height velocity (PHV)]. Materials and Methods: Thirty elite male youth soccer players aged 10–17 years from the Tunisian first division participated in this study. The players were divided into pre- (G1, n = 15) and post-PHV (G2, n = 15) groups. Both groups completed a similar 6-week training program with two sessions per week of four CoD exercises. All players completed the following tests before and after intervention: CS-YBT; 5 JT; 10, 30, and 15 m-CoD; and 15 m-CoD + B, and data were analyzed using ANCOVA. Results: All 30 players completed the study according to the study design and methodology. Adherence rate was 100% across all groups, and no training or test-related injuries were reported. Pre-PHV and post-PHV groups showed significant amelioration post-intervention for all dependent variables (after test > before test; p < 0.01, d = 0.09–1.51). ANOVA revealed a significant group × time interaction only for CS-YBT (F = 4.45; p < 0.04; η2 = 0.14), 5JT (F = 6.39; p < 0.02; η2 = 0.18), and 15 m-CoD (F = 7.88; p < 0.01; η2 = 0.22). CS-YBT, 5JT, and 15 m-CoD improved significantly in the post-PHV group (+ 4.56%, effect size = 1.51; + 4.51%, effect size = 1.05; and -3.08%, effect size = 0.51, respectively), more than the pre-PHV group (+ 2.77%, effect size = 0.85; + 2.91%, effect size = 0.54; and -1.56%, effect size = 0.20, respectively). Conclusion: The CoD training program improved balance, horizontal jump, and CoD without the ball in male preadolescent and adolescent soccer players, and this improvement was greater in the post-PHV players. The maturity status of the athletes should be considered when programming CoD training for soccer players.